A review of filled and pristine polycarbonate blends and their applications. (January 2018) - Kausar, Ayesha
Polycarbonate is an important thermoplastic polymer. Due to its high performance, polycarbonate has a range of engineering applications in construction, automotive, aircraft, data storage, electrical, and telecommunication hardware. However, polycarbonate's use is limited in advanced applications due to limitations, such as strong hydrophobicity, relatively limited chemical functionality, high melt viscosity, notch sensitivity of mechanical properties, and relative softness. Blending with other thermoplastic polymers improves its physical characteristics. The present review outlines up-to-date developments concerning the design and application of polycarbonate blends. A particular emphasis has been given to establish polycarbonate blends such as:  polycarbonate/polyethylene  polycarbonate/poly(methyl methacrylate)  polycarbonate/poly(vinylchloride)  polycarbonate/ polystyrene  polycarbonate/polyurethane  polycarbonate/polyester  polycarbonate/poly(ɛ-caprolactone). To improve the polycarbonate blend properties, fillers including organic and inorganic reinforcement materials (carbon nanotube, montmorillonite nanoclay, and metal nanoparticle) have also been employed. Polycarbonate blend applications in biomedical, flame retardant, and membrane materials have also been reviewed. To fully exploit the future potential for polycarbonate-based engineering materials, the structure–property relationship and compatibilization mechanisms need to be further explored.